IMPLEMENTATION OF INDUSTRIAL RELATIONS DISPUTE RESOLUTION IN THE INDUSTRIAL RELATIONS COURT IN REALIZING JUSTICE AND LEGAL CERTAINTY (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
Based on Law No. 2 of 2004, the resolution of industrial relations disputes is mandated by PPHI. Disputes must first be resolved through consensus, a failure to which one party can file a lawsuit with the Industrial Relations Court. These disputes include differences of opinion that result in conflict between employers or a combination of employers and workers/laborers or trade/labor unions due to disputes over rights, interests, termination of employment relations, and disputes between trade unions and labor unions within one company. This research aims to evaluate the implementation of industrial relations dispute resolution in industrial relations courts and determine how it can be improved to ensure justice and legal certainty. The research method used was descriptive analysis with a normative juridical approach, focusing on statutory regulations, principles, and legal theories that govern the resolution of industrial relations disputes. The study found that the process of examining industrial relations disputes based on the provisions of civil procedural law often prolonged the time for settling cases, which was initially set to 50 working days. However, this extended period proved detrimental to workers/labourers and failed to provide a sense of justice and legal certainty.
Keywords: industrial relations disputes; work relationship; worker/laborers